Human rights failures in time of coronavirus pandemic - Sánchez, Marlenne (2020)
In the uncertainty of living in these times of COVID-19 pandemic, we wonder about what is really happening, regarding human rights in the discourse and its application by the State. What other reading can we give it. The objective of this essay is to motivate an infinity of questions and to bring different edges of scientific research linked to the worldwide appearance of the SARS-CoV-2 pandemic, from the perspective of the validity and respect of human rights, some of whose shortcomings have remained mainly exposed in Peru. After an initial contextualization of the subject, we describe the world situation in general and our country in particular, related to the appearance and spread of the infectious disease called COVID-19; in whose examination and reality there are insolvencies in the validity and observance of some human rights. These stem from problems of the country’s social and economic structure, which are now becoming more acute within the unprecedented situation that COVID-19 has brought us to. The inequality of opportunities, informality, poverty and migration, among other conditions, affect the health and life of the most vulnerable and needy in our country.